# Coded Inequalities - Logical Reasoning Part 1

Coded Inequalities is one of simplest topic in logical reasoning section. But without proper rules and understanding we find it difficult to solve We can expect 3 to 5 questions based on this topic in competition exams .So we come up with two parts series on coded inequalities.

In coded inequalities statement/expression consists of a group of elements along with the relationship among them, which may be given in coded form.
Before we start the discussing on the steps to be followed for solving these questions lets check the meaning of certain symbols first in below :-

A>B means A is greater than B

A<B means A is less than B

A=B means A is equal to B

A≥B means A is either greater than B or A is equal to B

A≤B means A is less than B or A is equal to B

For these expression we find that
> Greater
< less
= Equal
≥ greater than or equal
≤ less than or equal

It is very important to understand the meaning of these operators now we  try to find out conclusion from given statements:-

A>B>C means B>C(A is greater than B, C )
A≥B>C means A,B are greater than C and A can be greater than B or equal to C
A=B>C means A and B are equal and greater than C (A>C)
A<B<C means A is less than B and C (A<C)
A<BC means A is less than B and C and B is equal to C or B is less than C
A=B<C means A and B are equal and A ,B less than C
AB≥C means A is either equal to C or A is Greater than C
AB=C means A is either equal to or greater than C (A>C or A=C)
A≤B>C means we can’t find any relation between A and C
A>B<C Means there is not relation between A and C but A is greater than B and C is greater than B

### Exercise :

1.Statement
X>Y≥Z
Conclusion:
1.Z>Y
2.Y=Z
Solution :
From this statement X is greater than Y and Z and Y is greater or either equal to Z
So from this Second conclusion is correct .

2.Statement
D≥E>F=G
Conclusion
1.D>G
2.F>G
Solution:
From this statement
F is equal to G
E is greater than F
D is either greater than or equal to E
So from this we can conclude than D>G

3. Statement
B>J≥R>Z
Conclusion
1.J>Z
2.J=Z
Solution:
From this statement
R is greater than Z and
J is either greater than or equal to R
Sp J is greater than Z 